Research on the Fault Scene Analysis and Diagnosis System Structure for Full Automatic Operation Trains - LU Kai; HE Deqiang; XIAO Hongsheng; GUO Rui (Kongzhi Yu Xinxi Jishu)
Compared with traditional manned subway train, unattended train realizes fully automation throughout the process of operation. In this paper, scenes from outbound to direct line operation of train were separately researched, typical fault state scenes were analyzed and the structure system of train fault diagnosis was constructed. It provides a theoretical basis for the development of automatic train on-board fault diagnosis system.